Predicting leisure walking intentions among older adults in urban residential areas: extended Theory of Planned Behavior and Health Belief Model - Zhuge, Jinhui; Wan Mohamed, Wan S.; Abdul Shukor, Shureen F. (SAGE Publications, 2025)
Aim: This study aimed to examine the factors influencing leisure walking intention among older adults in urban residential areas, analyze their interrelationships, and propose strategies for promoting walking activities. Background: Understanding the factors influencing walking intentions among older adults is essential for developing interventions that enhance physical activity levels in an ageing society. A comprehensive approach that integrates psychological and environmental factors provides deeper insight into these influences. Methods: Data were primarily obtained from older adults aged 60 years and older residing in five residential areas in Guilin, China, selected based on construction time, population density, available facilities, and aesthetic design. Participants were recruited through assistance from residential management. After excluding questionnaires with ineligible ages, excessively short completion times, or uniform responses, 527 valid questionnaires were retained. Data analysis was constructed using structural equation modeling, integrating the Theory of Planned Behavior and the Health Belief Model. Reliability and validity of the questionnaire were evaluated through Cronbach’s alpha, composite reliability, factor loadings and average variance extracted. Results: The findings of this study revealed that among the factors influencing walking behavior intention, attitudes towards walking had the strongest positive effects. Perceived environmental barriers have a stronger negative impact on walking intention than perceived personal barriers. Conclusions: Improving residential walking facilities to reduce environmental barriers and enhancing community health education to reinforce health beliefs are effective strategies for promoting physical activity among older adults. These findings provide practical guidance for urban planning and public health initiatives.